Exposure to 'healthy' fast food meal bundles in television advertisements promotes liking for fast food but not healthier choices in children. Issue 6 (26th February 2015) - Boyland, Emma J.; Kavanagh-Safran, Melissa; Halford, Jason C. G.
Abstract : Due to regulatory changes, fast food companies often depict healthy foods in their television advertisements to children. The present study examined how exposure to advertising for 'healthy' meal bundles to children influenced the selection of food in children. A total of fifty-nine children (thirty-seven males) aged 7–10 years (8·8 (sd 0·9) years) took part in the present study. The within-participant, counterbalanced design had two conditions: control (exposure to ten toy adverts across two breaks of five adverts each) and experimental (the middle advert in each break replaced with one for a McDonald's Happy Meal ® depicting the meal bundle as consisting of fish fingers, a fruit bag and a bottle of mineral water). Following viewing of the adverts embedded in a cartoon, children completed a hypothetical menu task that reported liking for McDonald's food and fast food, in general. Nutritional knowledge, height and weight of the children were measured. There was no significant difference between the two advert conditions for the nutritional content of the meal bundles selected. However, children's liking for fast food, in general, increased after exposure to the food adverts relative to control ( P = 0·004). Compared to children with high nutritional knowledge, those with low scores selected meals of greater energy content (305 kJ) after viewing the food adverts ( P = 0·016). Exposure to adverts for 'healthy' meal bundles did not drive healthier choices in children, but did promote liking for fast food. These findings contribute to debates about food advertising to children and the effectiveness of related policies.